Industrial Relations with ukhuwwah (brotherhood), ‘adl (justice), and ihsan (benevolence) - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi; Ismail, Yusof; Firmansah, Yayan (Faculty of Economics and Management & Centre for Islamic Economics Studies (CIES), University of Darussalam Gontor, Indonesia, 2024)
Traditional perspectives on industrial relations argued that the persistent competition among different entities, including workers, capitalists, bureaucrats, and authorities, with the goal of reducing operating costs while maximising financial profits. In contrast, Islamic values such as ukhuwwah (brotherhood), ‘adl (justice), and ihsan (benevolence) place importance on establishing a harmonious and ethical relationship between employers and employees, which serves as a solid foundation for creating a positive work environment. This study used the grounded theory method through focused group discussion to explore the integration of Islamic values into the industrial relations of Islamic universities. It focuses on insights from participants who emphasised the significance of promoting positive human relationships, incorporating Islamic teachings, and maintaining a balance between procedural work and community-building activities. The study's findings suggest that incorporating these principles can establish a cohesive and morally upright work environment that is advantageous for both employees and organisations. Suggestions for the industrial relations unit, top management, board of governors, and the government involve cultivating strong unity through team-building, maintaining fairness with clear and open policies, and promoting excellence by supporting professional growth and empathetic work conditions.